PROFIL SISWA BERKEMAMPUAN MATEMATIKA TINGGI DALAM MEMECAHKAN SOAL CERITA POKOK BAHASAN ARITMATIKA SOSIAL - Fatmawati, Kamila Duwi; Trapsilasiwi, Dinawati; Yudianto, Erfan; Kristiani, Arika Indah; Hussen, Saddam (Department of Mathematics Education , University of Jember, 2019)
The problem-solving profile is a general description of the activities of solving mathematical problems carried out by students using the five stages of IDEAL model problem solving namely identifying problems, defining problems, finding solutions, implementing strategies, and reviewing and evaluating their effects. This becomes interesting when it is associated with mathematical abilities. This study aims to describe the profile of students with high mathematical ability in solving questions about the subject of Social Arithmetic. This type of research is qualitative research. Students with high mathematical ability were given two problem-solving test questions, then interviews were conducted to find out more in the process of solving them. The results obtained are students with high mathematical ability able to meet all the indicators of each stage of solving the IDEAL model. This can be seen from the results of the work provided and interviews conducted by researchers against these students.